Flux transfer event observation at Saturn's dayside magnetopause by the Cassini spacecraft. Issue 13 (6th July 2016) - Jasinski, Jamie M.; Slavin, James A.; Arridge, Christopher S.; Poh, Gangkai; Jia, Xianzhe; Sergis, Nick; Coates, Andrew J.; Jones, Geraint H.; Waite, J. Hunter
Abstract: We present the first observation of a flux rope at Saturn's dayside magnetopause. This is an important result because it shows that the Saturnian magnetopause is conducive to multiple X‐line reconnection and flux rope generation. Minimum variance analysis shows that the magnetic signature is consistent with a flux rope. The magnetic observations were well fitted to a constant‐ α force‐free flux rope model. The radius and magnetic flux content of the rope are estimated to be 4600–8300 km and 0.2–0.8 MWb, respectively. Cassini also observed five traveling compression regions (remote signatures of flux ropes), in the adjacent magnetosphere. The magnetic flux content is compared to other estimates of flux opening via reconnection at Saturn. Key Points: We present the first observation of a flux transfer event at Saturn which occurred during an increase in solar wind dynamic pressure Conditions at Saturn's magnetopause are at times conducive to multiple X‐line reconnection and flux rope generation MVA and modeling are used to determine that the FTE had a flux rope structure and a magnetic flux content of 0.2–0.8 MWb